NA Padangsidimpuan Dakwah Language Style on Facebook - Husniah Ramadhani Pulungan; Nikmah Sari Hasibuan; Rukiah Rukiah (Budapest International Research and Critics University, 2022)
NA Padangsidimpuan's da'wah language style on Facebook is analyzed because there has been a shift in da'wah style in this era of the industrial revolution 4.0. Initially, da'wah was carried out in the form of recitations, which in reality had shown that there was a lack of interest in NA who were millennials in participating in the study. This is known based on the statement of the leader himself who complained about the enthusiasm of members in attending the study that had been held. This research offers one of the innovations for NA to preach in the digital era through Facebook. The goal is to be closer to millennial NA who tend to live longer in cyberspace than in the real world. The use of this platform as a medium of da'wah and also involving all NA in practicing it has generated a very positive response. Through a da'wah-themed language style by giving an attractive hash (#), NA's da'wah on Facebook becomes more positive and interactive. In addition, NA members become more communicative and invite curiosity for those who see the status of their da'wah writings. Thus, useful da'wah has been realized by utilizing the media favored by today's millennials. Similar research can still be done from another point of view, such as from the point of view of netizens' comments in the comment’s column, it can be interesting research as well in the future.